Academic Performance and Procrastination: The Case of Education Students in Mindanao State University, Sulu, Philippines - Anuddin, Fermina Omar (Indonesian Community Empowerment Journal, 2021)
Academic is usually represented by the student delaying or postponing assignments resulting in late submissions and coupled with a general reduction in study time and inadequate preparation for examinations. This study aimed to describe the relationship of procrastination to academic performance in Education students of Mindanao State University, Sulu, Philippines. This study was a descriptive observational study and was conducted on 2nd year College of Education students, Mindanao State University, Sulu, Philippines. Sampling is carried out by purposive sampling. This research adopted the questionnaire academic procrastination Questionnaire (APQ). The researcher also asked the students to indicate their midterm grade in GEC 104 (Mathematics in the Modern World) in the questionnaire. The results of the study show the participants' responses on the scale of academic procrastination ranged from (3.71 - 2.02) with the highest for the item “I finish my duties in GEC 104 before the deadline”, whereas the lowest was for the item "I stop studying early in order to do more enjoyable things”. In conclusion, there is no relationship between procrastination behavior and academic performance in students at the College of Education, Mindanao State University, Sulu, Philippines.